1998
DOI: 10.1074/jbc.273.41.26269
|View full text |Cite
|
Sign up to set email alerts
|

BEGAIN (Brain-enriched Guanylate Kinase-associated Protein), a Novel Neuronal PSD-95/SAP90-binding Protein

Abstract: PSD-95/SAP90 is a synaptic membrane-associated guanylate kinase with three PDZ, one SH3, and one guanylate kinase (GK) domain. PSD-95/SAP90 binds various proteins through the PDZ domains and organizes synaptic junctions. PSD-95/SAP90 also interacts with the postsynaptic density (PSD) fraction-enriched protein, named SAPAP (also called GKAP and DAP), through the GK domain. SAPAP is Triton X-100-insoluble and recruits PSD-95/SAP90 into the Triton X-100-insoluble fraction in the transfected cells, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0
2

Year Published

1999
1999
2002
2002

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 30 publications
(25 reference statements)
1
77
0
2
Order By: Relevance
“…MAGUIN-1 is Triton X-100-insoluble and recruits PSD-95/ SAP90 and S-SCAM into the Triton X-100-insoluble fraction. SAPAP has a similar activity for PSD-95/SAP90 and S-SCAM (22). 2 These findings suggest that PSD-95/SAP90 and S-SCAM are connected to the Triton X-100-insoluble structures via the PDZ domain by MAGUIN-1 and via the GK domain by SAPAP.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…MAGUIN-1 is Triton X-100-insoluble and recruits PSD-95/ SAP90 and S-SCAM into the Triton X-100-insoluble fraction. SAPAP has a similar activity for PSD-95/SAP90 and S-SCAM (22). 2 These findings suggest that PSD-95/SAP90 and S-SCAM are connected to the Triton X-100-insoluble structures via the PDZ domain by MAGUIN-1 and via the GK domain by SAPAP.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, MAGUIN-1 may also bind Raf kinase and links it to PSD-95/ SAP90 and S-SCAM. The yeast two-hybrid screening using the GK domain of PSD-95/SAP90 revealed SPA-1-like protein besides SAPAP and BEGAIN (22). SPA-1 is a GAP protein for Rap1 (45), and Rap1 plays roles in the MAPK pathway (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anchoring proteins also act as scaffolds by arranging signal molecules in a certain order that is determined by the specific binding of signal molecules to different PDZ domains. Recent studies have revealed that the GK domain of PSD/SAP family proteins, although it has no guanylate kinase activity , acts as a binding domain for SAPAPs/GKAP/PAP Satoh et al, 1997;Takeuchi et al, 1997), MAP1A (Brenman et al, 1998), BEGAIN (Deguchi et al, 1998) or the kainate receptor (Garcia et al, 1998). However, the functional role of the GK domain has remained largely unclarified.…”
Section: Discussionmentioning
confidence: 99%
“…The stable transformants of CHO cells expressing PSD-95/SAP90 were as previously described (Deguchi et al 1998). Cells of two 10-cm dishes were collected after 48 h of culture and homogenized by sonication in 0.3 mL of 20 mM Hepes/NaOH pH 7.4.…”
Section: Subcellular Fractionation Of Cho Cellsmentioning
confidence: 99%